IDENTIFIKASI MISKONSEPSI PADA MATERI PANCA INDERA MANUSIA MENGGUNAKAN METODE CERTAINTY OF RESPONSE INDEX (CRI) PADA KELAS IV SEKOLAH DASAR - Marfilinda, Riri; Vebrianti, Vebi (LP2M Universitas Adzkia, 2024)
This study aims to describe misconceptions held by fourth-grade elementary school students regarding the concept of human sensory organs. The research employed a qualitative descriptive approach using the Certainty of Response Index (CRI) method to measure students’ confidence in their answers. The subjects consisted of 11 students selected through diagnostic tests and interviews. The results showed that the highest misconception occurred in the concept of the sense of sight (eye) at 74.5%, while the lowest was in the general understanding of the human senses at 37.83%. The causes of these misconceptions stemmed from internal factors, such as associative thinking and incorrect intuition, as well as external factors, including teaching methods, textbooks, and learning context. Based on these findings, it can be concluded that misconceptions about the concept of human sensory organs are still present among fourth-grade students and require targeted instructional interventions.